MOTOR DEVELOPMENT OF STUDENTS PRACTICING SWIMMING AND STUDENTS OF PHYSICAL EDUCATION SCHOOL (Fiep Bulletin - online, 2013)
Swimming is undoubtedly one of sports most primitive and which currently has been gaining ever more adherents. Currently on the basis of results from major Brazilian swimmers and the benefits it provides the practitioner the number of fans is growing every day. In view of the development engine it becomes a very important strategy, because through the liquid medium, the child receives a variety of different stimuli both the water itself but also the activities and materials used. And when we talk about motor development the child needs to be involved with the largest possible number of experiments for developing all their genetic potential. So the purpose of this study was to analyze the influence of swimming in the motor development of children from 4 to 7 years old age group that understands the fundamental motor skills. The sample consisted of 14 children of both sexes being 7 practicing swimming at least 6 months and 7 participants only school Physical Education at the School of Application. We performed a shooting of six fundamental motor skills, which are analyzed using the protocol for assessing FMPAI. The results show us that children who had practiced swimming in the vast majority of the movement in elementary and mature stages. By contrast the only participating school of Physical Education school showed up in the vast majority in the elementary stage, but the movements jump and perhaps there was a predominance in the early stage. We therefore a trend that children who practice swimming at the present stage of development advocated in the literature and in some cases at a stage above.
Keywords: Swimming; motor development; fundamental motor skills.